Study of genetic factors and temperature influence on sex determination and differentiation in turbot - Robledo Sánchez, Diego
Sex, as intuitive and simple as it may seem to us, poses some of the most interesting and complex questions when studying life. Sex is an intrinsic characteristic of most eukaryote species which eventually has led to the appearance of two differentiated adult phenotypes or sexes, males and females. This distinction rules a huge part of our lives and is the origin of important evolutionary processes based on intra-sex competition or inter-sex conflict due to sexual antagonism. Furthermore, sex is an important character for a plethora of species involved in human activities, for example in aquaculture many fish species present sex size dimorphisms where one sex grows faster than the other, and so knowing how sex is determined in each species is of the outmost interest. Traditionally, sex determination has been considered a cascade process with a master gene at the top, but recent findings have suggested that, instead, it might be a network process where different genetic and environmental factors can alter gonad fate, which in turn would be connected with a huge number of different sex determination mechanisms in vertebrates, especially in poikiloterms. In this new view of sex, the different players involved in sex differentiation gain relevance and their study may help us understanding how the fate of the gonad is determined. In this work, we have studied sex differentiation in turbot, a flatfish with a marked sex dimorphism where females grow faster than males. This species presents genetic sex determination, but also temperature effects on sex ratios have been reported, which seem to be family-dependant. Our aim was to study sex differentiation in turbot to gain knowledge about how sex is determined in this species and also in a broader sense in fish. This work consists of expression studies in turbot gonads using two different techniques: real-time PCR and microarrays. First of all, the real time PCR technique was setup for gonad development studies in turbot. The different methods available for reference gene ...